Heat and Mass Transfer - Karwa, Rajendra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This textbook presents the classical treatment of the problems of heat transfer in an exhaustive manner with due emphasis on understanding of the physics of the problems. This emphasis is especially visible in the chapters on convective heat transfer. Emphasis is laid on the solution of steady and unsteady two-dimensional heat conduction problems. Another special feature of the book is a chapter on introduction to design of heat exchangers and their illustrative design problems. A simple and understandable treatment of gaseous radiation has been presented. A special chapter on flat plate solar air heater has been incorporated that covers thermo-hydraulic modeling and simulation. The chapter on mass transfer has been written looking specifically at the needs of the students of mechanical engineering. The book includes a large number and variety of solved problems with supporting line diagrams. The author has avoided duplicating similar problems, while incorporating more application-based examples. All the end-of-chapter exercise problems are supplemented with stepwise answers. Primarily designed to serve as a complete textbook for undergraduate and graduate students of mechanical engineering, the book will also be useful for students of chemical, automobile, production, and industrial engineering streams. The book fully covers the topics of heat transfer coursework and can also be used as reference for students preparing for competitive graduate examinations. .
List of Symbols -- Chapter 1: Introduction -- Chapter 2: One Dimensional Steady State Heat Conduction -- Chapter 3: Extended Surfaces (Fins) -- Chapter 4: Conduction with Heat Generation -- Chapter 5: Steady-State Two Dimensional Heat Conduction -- Chapter 6: Unsteady or Transient Heat Conduction -- Chapter 7: Convective Heat Transfer -- Chapter 8: Empirical Relations for Forced Convection Heat Transfer -- Chapter 9: Empirical Relations for Natural or Free Convection -- Chapter 10: Laws of Thermal Radiation -- Chapter 11: Exchange of Thermal Radiation between Surfaces Separated by Transparent Medium -- Chapter 12: Heat Transfer in Absorbing and Emitting Media (Gaseous Radiation) -- Chapter 13: Heat Transfer in Condensing Vapours and Boiling Liquids -- Chapter 14: Heat Exchangers -- Chapter 15: Mass Transfer -- Chapter 16: Special Topic: Performance of Solar Air Heater -- Appendix A: Conversion Factors -- Appendix B: Short Questions -- Bibliography.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Electric power production; Chemistry, Technical; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics; Electrical Power Engineering; Mechanical Power Engineering; Industrial Chemistry